(untitled) (International Journal of Academic Research in Progressive Education and Development, 2022)
This paper aims to examine the human development programs at Yayasan Dakwah Islamiah Malaysia (YADIM) and evaluate them from the perspective of Islamic-based development. More specifically, this paper aims to identify human development programs implemented by YADIM. This study also analyses the human development program based on aspects of philosophy, principles, and goals of Islamic -based development. As a result of the analysis, this study summarizes the concept, principles and development goals of the human development program implemented. The paper uses a qualitative content analysis method that is by using data obtained through in-depth interviews and secondary sources in the form of books, journals, reports, and other printed materials. This paper has successfully examined and discovered the human development programs implemented at YADIM that focus on the development of the younger generation. In addition, this paper also successfully examines the aspects of human development based on the teachings of Islam. These findings prove that Islamic-based human development programs are an appropriate method and proven capable of producing excellent and balanced Muslim individuals not only from the physical aspect alone but also the more important aspects namely spiritual, emotional, mental, and intellectual.